Hashimoto's Disease and Thyroid Cancer in Children: Are They Associated? - Penta, Laura; Cofini, Marta; Lanciotti, Lucia; Leonardi, Alberto; Principi, Nicola; Esposito, Susanna (Frontiers in Endocrinology, 2018)
Hashimoto’s thyroiditis (HT) is the most common cause of thyroid disease in children and adolescents. Along with significant modifications of thyroid function, HT in pediatric age can be accompanied by relevant thyroid structural alterations. Over time, benign thyroid nodules, carcinoma and, rarely, primary non-Hodgkin lymphoma can develop. However, the relationships between HT and neoplasms are poorly defined. The main aim of this paper is to discuss what is presently known regarding the coexistence of HT and thyroid tumours. Moreover, we attempt to define the pathogenesis of cancer development in children with HT. Literature analysis showed that despite its rarity and relatively promising prognosis, thyroid cancer is associated with HT. Although not all reasons for the coexistence of these diseases are clearly defined, children with HT should be considered at higher risk for thyroid cancer development. Strict correlations between high levels of serum TSH and anti-thyroid antibodies with cancer must be remembered. The same is true for the presence of nodules, especially if multiple nodules are present and ultrasonography and thyroid fine needle aspiration cytology should be promptly used in uncertain cases.